Bright fluorescent biocompatible Magnozyme nanoclusters for brain-cell in-vivo live imaging - Srivastava P.; Verma V.K.; Mehata A.K.; Singh M.; Sabbarwal S.; Muthu M.S.; Koch B.; Kumar M. (My University, 2025)
Multifluorescent, water-dispersible magnesium nanoclusters (Magnozyme) were obtained using a simple and economical synthesis procedure. The prepared particles were 4 nm in size, and they exhibited significant emission at 450, 545, and 628 nm with multiple excitations of 366,469 and 560 nm wavelengths. The prepared particle exhibited a maximum absolute quantum yield of 21.3, 6.8 % and 5 % in red, green and blue spectrum, respectively, with excellent photostability, good ionic strength tolerability, and broad-range pH stability. The prepared Magnozyme demonstrates 95 % cell viability in human glioma brain cell lines (U-87 MG) and can be used as a probe for cellular imaging. Furthermore, imaging with this brain cell revealed significant cytoplasmic accumulation in the red, green, and blue regions. The confocal Z-stack study revealed the presence of Magnozyme at a depth of the cellular level by capturing a series of images at different planer axes (z-axis). Furthermore, In-vivo toxicity assessments and in-vivo imaging in mice revealed the nontoxicity behavior of Magnozyme with their great staining ability in physiological conditions, confirming their candidature toward biological cell imaging/labeling purposes. © 2025 Elsevier B.V.